Pointwise lower bounds in growth spaces with little o conditions - Cuckovic, Zeljko; Taskinen, Jari (Mathematica Scandinavica, 2025)
Pointwise lower bounds on the open unit disc D for the sum of the moduli of two analytic functions f and g (or their derivatives) are known in several cases, like f,g belonging to the Bloch space B , BMOA or the weighted Hardy space H_ω ^∞ . We modify the proofs of two important cases, proved by Ramey-Ullrich and Abakumov-Doubtsov, for functions with little o growth conditions.